Fish diversity in the cascade of reservoirs along the Paranapanema River, southeast Brazil - Pelicice, Fernando Mayer; Azevedo-Santos, Valter M. [UNESP]; Henriques Esguicero, Andre Luiz; Agostinho, Angelo Antonio; Arcifa, Marlene Sofia (Soc Brasileira Ictiologia, 2018)
The Paranapanema River is a major tributary of the upper Parana river basin. Eleven hydropower dams regulate its main course, but no study has investigated fish diversity in these impoundments at the basin-scale. The present study investigated spatial patterns of richness, composition, and abundance of native (non-migratory and migratory) and non-native fishes in the cascade of reservoirs along the Paranapanema River. The study is based on data collected from 34 independent studies conducted in nine reservoirs (47 samples). The compilation recorded 161 species, being 111 native (14 migratory) and 50 non-native. Total richness ranged between 56 and 112 species/reservoir, with a mean of 72 (49.9 non-migratory, 8.1 migratory and 14 non-native). The number of non-migratory species showed no spatial trend along the cascade system, but migratory and non-native richness increased toward downstream reaches. We also observed spatial variation in species composition along the cascade system, but some non-native fishes were widely distributed. Migratory fishes showed low relative abundance (usually < 10%), while non-native species were common and more abundant, especially in reservoirs downstream. Our results revealed a high diversity of fishes in the cascade of impoundments, but indicated that migratory fishes are rare, while non-native species are common or dominant.
Keywords: Dam; Fish fauna; Longitudinal; Migratory fish; Non-native